When expanding (2a-3b)², we use the formula:
(a-b)² = a² - 2ab + b²
So, substituting 2a for a and -3b for b, we get:
(2a-3b)² = (2a)² - 2(2a)(-3b) + (-3b)²
= 4a² + 12ab + 9b²
Therefore, (2a-3b)² expands to 4a² + 12ab + 9b².
When expanding the brackets (2a-3b)²
3 answers
4a² + 12ab + 9b²
where is the minus sign ?
4a² - 12ab + 9b²
where is the minus sign ?
4a² - 12ab + 9b²
Apologies for the error in the previous answer. The correct expansion of (2a-3b)² is:
(2a-3b)² = (2a)² - 2(2a)(3b) + (-3b)²
= 4a² - 12ab + 9b²
So, the expansion of (2a-3b)² is 4a² - 12ab + 9b², with a negative sign between the second and third terms.
(2a-3b)² = (2a)² - 2(2a)(3b) + (-3b)²
= 4a² - 12ab + 9b²
So, the expansion of (2a-3b)² is 4a² - 12ab + 9b², with a negative sign between the second and third terms.